2013
DOI: 10.1080/03004430.2012.756874
|View full text |Cite
|
Sign up to set email alerts
|

Maternal stress and young children's behavioural development: a prospective pilot study from 8 to 36 months in a Finnish sample

Abstract: The relationship between maternal parenting stress and infant/toddler behavioural development was examined in a longitudinal pilot study. Fifty mothers reported parenting stress via the Parenting Stress Index -Short Form when their infants were eight months old. Parents subsequently rated their children's emotional and behavioural problems with the Child Behaviour Checklist at both 18 and 36 months of age. Preliminary results suggest that mothers reporting higher stress levels in their infant's first eight mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Mechanisms explaining intergenerational consequences of discrimination also deserve greater attention, as understanding mechanisms can identify ways to intervene. Maternal distress (e.g., pregnancy distress, anxiety, depression) adversely affects birth outcomes and infant development, 23,24 and discrimination is a stressor that causes psychological distress in addition to physical harm. 8 For example, depressive symptoms have been found to mediate the association of pregnant women’s discrimination experiences with lower birthweight.…”
Section: The Role Of Discriminationmentioning
confidence: 99%
“…Mechanisms explaining intergenerational consequences of discrimination also deserve greater attention, as understanding mechanisms can identify ways to intervene. Maternal distress (e.g., pregnancy distress, anxiety, depression) adversely affects birth outcomes and infant development, 23,24 and discrimination is a stressor that causes psychological distress in addition to physical harm. 8 For example, depressive symptoms have been found to mediate the association of pregnant women’s discrimination experiences with lower birthweight.…”
Section: The Role Of Discriminationmentioning
confidence: 99%
“…Second, although the focus of our study was specifically to assess subjective self-reported social anxiety symptoms using the SPAI and BFNE-S, future studies will include multi-method assessment (e.g., self-report and structured clinical interview), in order to more comprehensively assess the presence of SA symptoms and clinical diagnoses and in order to minimize the potential for self-report biases. Also, in previous studies [63], number of siblings in families was significantly associated with parental stress. We did not collect data on current family size.…”
Section: Studymentioning
confidence: 56%
“…According to Abidin (1992), parental stress is influenced by parent and child characteristics, partner relationships, and environmental factors. Parental stress has been found to negatively influence children's social, emotional, and behavioral development (Anthony et al 2005; Barroso et al 2018;Crnic et al 2005;Haapsamo et al 2013). A good parent-child relationship can protect against child behavior problems (Matthijssen et al 1998).…”
mentioning
confidence: 99%